Lipoprotein(a) and Pulmonary Embolism Severity-A Retrospective Data Analysis - Gressenberger, Paul; Posch, Florian; Pechtold, Moritz; Gütl, Katharina; Muster, Viktoria; Jud, Philipp; Riedl, Jakob; Silbernagel, Günther; Kolesnik, Ewald; Schmid, Johannes; Raggam, Reinhard B.; Brodmann, Marianne; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aim We aimed to investigate a correlation between PE severity and Lp(a) levels. Methods We performed a retrospective data analysis from our medical records of PE patients admitted to the University Hospital Graz, Austria. Patients with an Lp(a) reading within a 1-year interval before and after PE diagnosis were included. In accordance with the 2019 ESC guidelines for the diagnosis and management of acute PE, severity assessment was carried out classifying patients into four groups: low risk (LR), intermediate low risk (IML), intermediate high risk (IMH) and high risk (HR). The study period of interest was between January 1, 2002 and August 1, 2020. Results We analyzed 811 patients with PE, of whom 323 (40%) had low-risk PE, 343 (42%) had intermediate-low-risk PE, 64 (8%) had intermediate-high-risk PE, and 81 (10%) had high-risk PE, respectively. We did not observe an association between PE severity and Lp(a) concentrations. In detail, median Lp(a) concentrations were 17 mg/dL [25–75th percentile: 10-37] in low-risk PE patients, 16 mg/dL [10–37] in intermediate-low-risk PE patients, 15mg/dL [10–48] in intermediate-high-risk PE patients, and 13mg/dL [10–27] in high-risk PE patients, respectively (Kruskal-Wallis p = 0.658, p for linear trend = 0.358). Conclusion The current findings suggest no correlation between PE severity and Lp(a) levels.